Comparing policy strategies for a transition to a bioeconomy in Europe: The case of Italy and Germany. (November 2017) - Imbert, Enrica; Ladu, Luana; Morone, Piergiuseppe; Quitzow, Rainer
Graphical abstract: Overview of the analytical framework for the comparison of policy strategies. Abstract: Grand societal challenges call for a transition from a society based on finite fossil resources towards a bio-based economy, based on renewable resources. Such a transition should involve not only the energy sector, but also the manufacturing sector. As acknowledged in the European Bioeconomy Strategy, the promotion of a bioeconomy is dependent on policy efforts across a wide spectrum of policy spheres. In the literature on sustainability transitions, this insight is captured in the increasing interest in the concept of policy mixes or policy strategies for promoting transitions to more sustainable modes of production and consumption. In this paper, we present a comparative analysis of bioeconomy strategies in Germany and Italy with a focus on the bioplastics sector. The paper adds to the existing literature on policy mixes by extending the concept of a policy strategy and applying it for the purpose of the comparative analysis. Moreover, the analysis is linked to the discussion on multi-level systems of governance in the European Union. A key finding is that linkages between the two policy strategies via policy making within the European Union have helped in reinforcing the nascent transition to a bio-based economy in Europe.